2011
DOI: 10.1542/peds.2011-0520
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a School Nurse–Delivered Smoking-Cessation Intervention for Adolescents

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Most adolescent smokers want to quit and make serious attempts to quit. However, few seek medical assistance, and most are unsuccessful in their efforts to stop. Therefore, accessible, effective treatment approaches are needed for adolescents who want to quit smoking. WHAT THIS STUDY ADDS:Results demonstrate that a brief smoking-cessation intervention delivered by school nurses in the school health setting is feasible and moderately effective in helping adolescents to stop smoking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 23 publications
1
38
0
4
Order By: Relevance
“…The pooled absolute RD was Ϫ0.04 (CI, Ϫ0.09 to 0.01). A sensitivity analysis that included the 4 trials that involved tailored intervention components for baseline smokers, 12-month follow-up, and similar definitions of baseline smoking (15,16,29,33) yielded a consistent result. …”
mentioning
confidence: 73%
See 4 more Smart Citations
“…The pooled absolute RD was Ϫ0.04 (CI, Ϫ0.09 to 0.01). A sensitivity analysis that included the 4 trials that involved tailored intervention components for baseline smokers, 12-month follow-up, and similar definitions of baseline smoking (15,16,29,33) yielded a consistent result. …”
mentioning
confidence: 73%
“…No primary care-relevant trials were identified that assessed health outcomes or examined subsequent rates of adult smoking. We identified 18 trials (reported in 22 publications) that examined the efficacy of primary carerelevant interventions in preventing tobacco use initiation or promoting cessation among young persons (Appendix Table 1, available at www.annals.org) (15)(16)(17)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). We examined all 18 trials for harms related to the intervention and 1 additional trial (37) that reported the harms of bupropion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations